2018
DOI: 10.3389/fphys.2018.00972
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of Maximal Heart Rate in Hypoxia: Mechanisms and Clinical Importance

Abstract: The use of exercise intervention in hypoxia has grown in popularity amongst patients, with encouraging results compared to similar intervention in normoxia. The prescription of exercise for patients largely rely on heart rate recordings (percentage of maximal heart rate (HRmax) or heart rate reserve). It is known that HRmax decreases with high altitude and the duration of the stay (acclimatization). At an altitude typically chosen for training (2,000-3,500 m) conflicting results have been found. Whether or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 194 publications
(249 reference statements)
1
32
1
Order By: Relevance
“…At rest, a hypoxic stimulus increases sympathetic activity and reduces parasympathetic regulation [20], elevating HR and decreasing HRV [40]. In addition, during exercise HR is higher at any similar sub-maximal exercise intensity and decreased ad maximal intensities [11,26]. It has been shown that, for sufficiently high exercise intensities ( > 50 % V O 2 max), hypoxia does not exert an additional influence upon HRV [41], due to the already substantial exercise-induced vagal withdrawal and sympathetic activation [42].…”
Section: Cardiac Autonomic Modulation Responses During Exercise and Rmentioning
confidence: 99%
See 2 more Smart Citations
“…At rest, a hypoxic stimulus increases sympathetic activity and reduces parasympathetic regulation [20], elevating HR and decreasing HRV [40]. In addition, during exercise HR is higher at any similar sub-maximal exercise intensity and decreased ad maximal intensities [11,26]. It has been shown that, for sufficiently high exercise intensities ( > 50 % V O 2 max), hypoxia does not exert an additional influence upon HRV [41], due to the already substantial exercise-induced vagal withdrawal and sympathetic activation [42].…”
Section: Cardiac Autonomic Modulation Responses During Exercise and Rmentioning
confidence: 99%
“…Despite its promise, acute hypoxic exercise can result in altered physiological responses [11][12][13] and in increased exercise-induced homeostatic perturbation [14,15], that must be taken into account when prescribing exercise training. Particularly, both external (e. g. exercise load) and internal (e. g. heart rate) markers, commonly used for setting exercise intensity [16], are affected by acute hypoxia, making exercise prescription more challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These uniform changes suggest that there must be other reasons that account for the diverse changes in SV for subjects with different levels of baseline HRs after acute HA exposure. The increase in HR was more pronounced in subjects with a low baseline HR than in those with a high baseline HR, which might be attributed to the progressive decrease in maximal heart rate or heart rate reserve with increasing hypoxia [21]; however, the LV myocardial systolic velocity (S′) also increased in these low baseline HR subjects following acute HA exposure, which led to an increased LVEF, and consequently, the SVi was maintained. Moreover, the resting heart rate was positively correlated with LV S′ as well as E′, independent of sex and age [22].…”
Section: Discussionmentioning
confidence: 90%
“…Up to altitudes ~4,000 m the loss of aerobic capacity in hypoxia is determined by a decrease in arterial oxygen saturation (SaO 2 ) and thus arterial oxygen concentration (CaO 2 ) and mass arterial oxygen flux (CaO 2 x cardiac output = QaO 2 ) (Amann & Calbet, 2008;Chapman, Emery, & Stager, 1999;Chapman, Stager, Tanner, Stray-Gundersen, & Levine, 2011;Ferretti, Moia, Thomet, & Kayser, 1997). However, during exercise in more severe hypoxia (above ~4,000 m), when SaO 2 drops below 80 % (Wagner, 2000), there are unexplained reductions in both maximum heart rate and cardiac output (Amann & Kayser, 2009;Boushel et al, 2001;Kayser, Narici, Binzoni, Grassi, & Cerretelli, 1994;Mourot, 2018). The impaired maximal cardiac function at peak exercise in hypoxia is restored rapidly by increasing PiO 2 to normoxic levels, enabling heart rate and cardiac output to further increase with increasing exercise intensity.…”
Section: Introductionmentioning
confidence: 99%